2016
DOI: 10.1016/j.jid.2016.02.797
|View full text |Cite
|
Sign up to set email alerts
|

754 A crosstalk between the alpha and beta adrenergic receptors regulates keratinocyte migration

Abstract: Chronic venous leg ulcers (VLUs) are an increasingly prevalent unmet clinical challenge. Despite their high associated morbidity and mortality, the bioengineered bilayered living cellular construct (BLCC) remains the only VLU therapy FDA-approved for efficacy in 15 years, yet its healing-promoting mechanisms are not well-understood. We hypothesized that signals of the BLCC reverse the non-healing into healing-like phenotype by targeting cellular processes recognized as hallmarks of healing impairment in VLUs: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous reports showed that circadian oscillation of leukocyte distribution disappears in Adrb2 −/− mice, 12,17 and not only immune cells but also keratinocytes and fibroblasts express this receptor. 26,27 This issue should be addressed using cell-specific targeting of Adrb2 in future.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that circadian oscillation of leukocyte distribution disappears in Adrb2 −/− mice, 12,17 and not only immune cells but also keratinocytes and fibroblasts express this receptor. 26,27 This issue should be addressed using cell-specific targeting of Adrb2 in future.…”
Section: Discussionmentioning
confidence: 99%